(untitled) (International Journal of Engineering and Computer Science, 2016)
In smart cities, the wide variety of use cases spans from traffic management to water distribution.This is an important issue for managing traffic in an urban environment like smart cities.For solving this, Internet of Things(IoT) should be used.IoT used network of physical objects that feature an IP address for internet connectivity.Reservation-based system,Connected and Automated Vehicles(CAV) and smart parking system are proposed as a part of traffic management by using IoT.Sensing and classifying roadway obstacles provides accident free environment and also a smooth drive to the vehicles.This paper is a survey on traffic management in smart cities which is useful for traffic management in smart cities. Survey involves different traffic management schemes by using IoT.